Accuracy and Reliability of the Ankle Brachial Index Measurement Using a Multicuff Oscillometric Device Versus the Doppler Method. (September 2020) - Ichihashi, Shigeo; Desormais, Ileana; Hashimoto, Tomoko; Magne, Julien; Kichikawa, Kimihiko; Aboyans, Victor
Abstract : Objective: Ankle brachial index (ABI) is widely used for the diagnosis of lower extremity artery disease (LEAD). The purpose of this prospective study was to validate the diagnostic ability and reproducibility of a four cuff automated oscillometric device vs. the Doppler method. Methods: Patients with suspected LEAD or asymptomatic individuals at risk because of the presence two or more cardiovascular risk factors were enrolled. For each patient, Doppler and oscillometric ABI measurements were repeated by two observers to address intra- and interobserver reproducibility. Results: In total, 118 patients were evaluated. The prevalence of Doppler ABI (Dop-ABI) ≤ 0.90 was 45.8%. Taking the Dop-ABI as the reference, the sensitivity, specificity, accuracy, positive and negative predictive values of oscillometric ABI (Osc-ABI) during the first measurement by the first observer were 89.1%, 94.4%, 94.1%, 91.8%, and 92.4%, respectively. The concordance for diagnosing ABI ≤0.90 between methods was excellent (kappa coefficients ranging from 0.80 to 0.88 with different observers). Intra-observer reproducibility assessed by intraclass correlation coefficient (ICC) between methods were 0.94 for observer 1 and 0.96 for observer 2. The intra-observer reproducibility using the same method was also excellent (ICC 0.94, 95% confidence interval [CI] 0.91–0.95) for Dop-ABI and 0.95 (95% CI 0.93–0.97) for Osc-ABI). The ICC for interobserver reproducibility using the same method was 0.95 (95% CI 0.92–0.96) for Dop-ABI and 0.96 (95% CI 0.94–0.97) for Osc-ABI. Conclusion: This study validates the excellent diagnostic performances of a four cuff oscillometric device specifically designed for screening for LEAD. The simple measurement method could therefore be advocated in primary care where fast, easy, and reliable methods are suitable.